Polish Question in the Discourse of Russian Pre-Revolutionary Social Thought - M. S. Belousov; Y. S. Abdullaev; V. A. Chikina (Научный диалог, 2019)
An attempt is made to reveal the key elements of the discourse of ethnic diversity management in Russian pre-revolutionary social thought. Numerous texts published by representatives of various sociopolitical views (Westerners, Slavophiles, liberals, conservatives, populists and socialists) devoted to the description and assessment of the policy of the Russian government in relation to national regions in the period under review are analyzed. The study was conducted on the basis of the analysis of mainly English-language scientific literature. Poland was chosen as a model region, that is, the main attention in the article is focused on the Polish question. The choice of this national outskirts is due to the following: on the one hand, it compelled the most close attention of representatives of the Russian pre-revolutionary social movement, and on the other, this territory was the place of testing of various incorporation practices by the Russian government. The study showed that, despite different political views and ideological platforms, Russian intellectuals clearly defined the intentions of the authorities, which consisted in the gradual integration of the periphery into the common imperial space, first on the administrative-legal, and then the cultural field. It is shown that the undulating nature of this process was absolutely opportunistic.